2006
DOI: 10.1002/sia.2256
|View full text |Cite
|
Sign up to set email alerts
|

Cylindrical and ring‐shaped tubulin assemblies as metallization templates explored by FESEM/EDX and SFM

Abstract: Tubulin self-assembles in vitro in highly ordered polymorphic protein structures such as tubules or rings, which can be further utilized as a template to control the deposition of metal nanoparticles or for continuous metal coatings. Template-directed alignment of particles or a continuous coverage is provided by metal salt incubation followed by a subsequent reduction procedure. We exploited field emission scanning electron microscopy (FESEM) with different electron detectors (inlens-SE, BSE, TE) for morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
(8 reference statements)
0
7
0
Order By: Relevance
“…For example, tubulin subunits have been polymerized and fixed using glutaraldehyde into extended microtubule templates that facilitate the formation of 1-D metallic nanostructures . Depending on the reduction method, Unger and co-workers have shown that either Ag nanowires or structures consisting of an array of densely packed AgNPs or AuNPs could be formed from these microtubule templates. , Interestingly, tubulin can also be coaxed into forming ring-like assembles which can be metallized to generate Ag nanostructures. , Another cytoskeletal protein that has been used to synthesize metal nanowires is actin. Willner and colleagues have shown the attachment of ∼1.4 nm AuNPs to actin monomers (G-actin) followed by polymerization into the filamentous form of actin (F-actin) using adenosine triphosphate (ATP) .…”
Section: Synthesis With Solution-phase Templatesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, tubulin subunits have been polymerized and fixed using glutaraldehyde into extended microtubule templates that facilitate the formation of 1-D metallic nanostructures . Depending on the reduction method, Unger and co-workers have shown that either Ag nanowires or structures consisting of an array of densely packed AgNPs or AuNPs could be formed from these microtubule templates. , Interestingly, tubulin can also be coaxed into forming ring-like assembles which can be metallized to generate Ag nanostructures. , Another cytoskeletal protein that has been used to synthesize metal nanowires is actin. Willner and colleagues have shown the attachment of ∼1.4 nm AuNPs to actin monomers (G-actin) followed by polymerization into the filamentous form of actin (F-actin) using adenosine triphosphate (ATP) .…”
Section: Synthesis With Solution-phase Templatesmentioning
confidence: 99%
“…554,555 Interestingly, tubulin can also be coaxed into forming ring-like assembles which can be metallized to generate Ag nanostructures. 556,557 Another cytoskeletal protein that has been used to synthesize metal nanowires is actin. Willner and colleagues have shown the attachment of ∼1.4 nm AuNPs to actin monomers (G-actin) followed by polymerization into the filamentous form of actin (F-actin) using adenosine triphosphate (ATP).…”
Section: Biological and Organic Templatesmentioning
confidence: 99%
“…To verify and develop this possibility, further experimental quantification of MT electrical properties is required. In addition to creating hybrid bio-nanoelectronic devices, implantable subcellular structures based on MTs can be engineered for applications such as neuroregeneration, memory augmentation, or targeted drug delivery. If the challenges outlined above can be overcome, then the potential of MTs to reduce the complexity of microelectromechanical systems, while simultaneously enhancing their versatility and functionality, is monumental and can create avenues for a wide spectrum of applications.…”
Section: Perspectivesmentioning
confidence: 99%
“…Further symmetry breaking would lead to different 3D structures such as double-wall , ring-shaped, sheet-like, C-shaped and S-shaped ribbons, and hoop structures as seen during tubulin polymerization experiments [21][22][23].…”
Section: The Dynamical Equationsmentioning
confidence: 99%
“…In this paper, however, we based our model on fundamental biochemical reactions that are occurring during microtubule's assembly and disassembly processes. This enables us to derive a nonlinear system particular, our model explains the continuum symmetry breaking of an isotropic pool of tubulin dimers that leads to formation of experimentally observed 3D structures such as ring-shaped or filaments [21][22][23]. We believe that this treatment is necessary to address the fundamental issues about the observed dynamical behavior of MTs.…”
Section: Introductionmentioning
confidence: 99%